Analysing sporting goods manufacturers’ environmental management tools - Ráthonyi , Gergely; Ráthonyi-Ódor , Kinga (Applied Studies in Agribusiness and Commerce, 2015)
Organizations around the developed world are facing pressure from governments, international agreements, society and various stakeholders, to improve their behavior towards the natural environment. The application of environmental management tools may be an important step towards sustainability and the preservation of environmental values, however marketing could be the key – with the help of information and communication technologies (ICT) – in publicizing and spreading these ideas thus forming customers’, stakeholders’ attitude in this respect.The aim of this study was to define the concept of environmental consciousness and environmentally conscious behaviour, then to present the shift the traditional marketing philosophy towards the sustainable marketing approach, finally to analyse two top sporting goods manufacturers’ (Nike, Adidas) environmental management tools with the help of data gained from their web sites, reports, case studies. Interpreting environmental consciousness is difficult without knowing the attitude to it. In spite of that it is important to distinguish between environmental consciousness and environmentally conscious attitude, because consciousness often appears in attitude influenced by other, outer effects.The environmental conscious attitude of companies in itself is not enough for making use of the advantages deriving from a positive environmental concern. They need to pursue more active communication, to „green” the whole of marketing activities. Thus marketing seems a possible means to naturalize and expand environmental protection both among customers and in company practice. According to the analysed companies, we need to say, that they are commitment with the environmental protection. They are used state-of-theart technologies to make their activity greener and introduce these with full particulars, examples e.g. ColorDry technologies, Better Cotton, The Framaprene ECO heel. Either Nike, Inc., or Adidas Group realised that ICT have the ability to improve efficiency and cut the use of material goods, thus reducing energy demands and the burden upon the environment.JEL code: Q01